Space is the place: European jazz festivals as cultural heritage sites. Issue 6 (2nd June 2020) - Whyton, Tony
ABSTRACT: The JPI-Heritage Plus supported Cultural Heritage and Improvised Music in European Festivals (CHIME) project was established to examine the workings of jazz festivals and their relationship to cultural heritage as discursive practice. Jazz festivals occupy a significant – if undervalued – place in the ecologies of Europe's cultural heritage, with their dynamic and synergetic relationship to spaces and cultural sites. Drawing on a number of case studies and interviews with members of the Europe Jazz Network, this article presents a typology of European jazz festivals and cultural heritage sites that can be used to inform the different ways in which jazz offers meaning to specific groups and locations. By viewing jazz festivals through the lens of cultural heritage, we can begin to challenge reified presentations of heritage that promote uncomplicated interpretations of nations, people and their associated cultural narratives. Festivals offer meaning to specific groups through acts of remembrance or commemoration, they have the potential to engage with a multitude of voices, and their locations enable people to negotiate a sense of belonging or to (re)consider their place in the world.